Advances in Lanthanum Ferrite-Based Sensors: A Comprehensive Review - Yadav A.K.; Singh P.; Pandey R. (My University, 2025)
Lanthanum ferrite has emerged as a promising material for the development of advanced sensor technologies due to its unique electrical, magnetic, and optical properties. This comprehensive review explores the recent advancements in lanthanum ferrite-based sensors, highlighted their potential applications in various fields, including gas sensing, humidity sensing, biomedical diagnostics and environmental monitoring. The review delves into the underlying principles of lanthanum ferrite sensors, their fabrication techniques, and the strategies employed to enhance their sensitivity, selectivity, and stability. Particular emphasis is placed on the integration of lanthanum ferrite with complementary materials and the utilization of advanced characterization techniques to unlock the full potential of these sensor systems. Current challenges and future research directions in this rapidly evolving field are also discussed, aiming to provide a roadmap for further developments and widespread adoption of lanthanum ferrite-based sensors. © 2025 Wiley-VCH GmbH.